The dragon prince. [4], Dreamer's nightmare - Ehasz, Aaron; Andelfinger, Nicole; Giehl, Devon; Richmond, Justin (Dragon Prince, 2024)
In the quiet town of Noct in the Human Kingdom of Katolis, a storm has been brewing. By the time young princes Callum and Ezran arrive, the community is in a state of panic. A mysterious force has been sweeping through the town, putting any adult who encounters it into a deep sleep. Children recount what they saw--some describe a beast, others a dragon, some even mention an elf--but is there truly something sinister at work, or have their imaginations gotten the best of them? While King Harrow, Aunt Amaya and the rest of the adults attempt to solve the mystery, Callum and Ezran meet compelling forces of their own. While each prince has something to prove, they will need to work together if they want to get to the bottom of things. Can Callum and Ezran uncover the source of the chaos before all of Noct is lost to a nightmare?